A Platform for the Development and the Validation of HW IP Components Starting from Reference Software Specifications. (19th January 2008) - Lucarz, Christophe; Mattavelli, Marco; Dubois, Julien
Abstract : Signal processing algorithms become more and more efficient as a result of the developments of new standards. It is particularly true in the field video compression. However, at each improvement in efficiency and functionality, the complexity of the algorithms is also increasing. Textual specifications, that in the past were the original form of specifications, have been substituted by reference software which became the starting point of any design flow leading to implementation. Therefore, designing an embedded application has become equivalent to port a generic software on a, possibly heterogeneous, embedded platform. Such operation is getting more and more difficult because of the increased algorithm complexity and the wide range of architectural solutions. This paper describes a new platform aiming at supporting a step-by-step mapping of reference software (i.e., generic and nonoptimized software) into software and hardware implementations. The platform provides a seamless interface between the software and hardware environments with profiling capabilities for the analysis of data transfers between hardware and software. Such profiling capabilities help the designer to achieve different implementations aiming at specific objectives such as the optimization of hardware processing resources, of the memory architectures, or the minimization of data transfers to reach low-power designs.